Morphological Characteristics and Comparative Transcriptome Analysis of Three Different Phenotypes of Pristella maxillaris - Bian, Fangfang; Yang, Xuefen; Ou, Zhijie; Luo, Junzhi; Tan, Bozhen; Yuan, Mingrui; Chen, Tiansheng; Yang, Ruibin (Frontiers in Genetics, 2019)
Pristella maxillaris is known as the X-ray fish based on its translucent body. However, the morphological characteristics and the molecular regulatory mechanisms of these translucent bodies are still unknown. In this study, the following three phenotypes, a black-and-gray body color or wild-type (WT), a silvery-white body color defined as mutant I (MU1), and a fully transparent body with a visible visceral mass named as mutant II (MU2), were investigated to analyze their chromatophores and molecular mechanisms. The variety and distribution of pigment cells in the three phenotypes of P. maxillaris significantly differed by histological assessment. Three types of chromatophores (melanophores, iridophores, and xanthophores) were observed in the WT, whereas MU1 fish were deficient in melanophores, and MU2 fish lacked melanophores and iridophores. Transcriptome sequencing of the skin and peritoneal tissues of P. maxillaris identified a total of 166,089 unigenes. After comparing intergroup gene expression levels, more than 3,000 unigenes with significantly differential expression levels were identified among three strains. Functional annotation and Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses of the differentially expressed genes (DEGs) identified a number of candidates melanophores and iridophores genes that influence body color. Some DEGs that were identified using transcriptome analysis were confirmed by quantitative real-time PCR. This study serves as a global survey of the morphological characteristics and molecular mechanism of different body colors observed in P. maxillaris and thus provides a valuable theoretical foundation for the molecular regulation of the transparent phenotype.